Acrylic foam tape and preparation method thereof
By using raw materials such as terpene resin, organic rigid particles PA6 and bacterial cellulose in acrylic foam tape, the cohesion strength of acrylic pressure-sensitive adhesives is improved, and the peeling residue problem is solved, ensuring the adhesion of new parts and electronic products is ensured. Connect performance.
Patent Information
- Application Number
- CN202210568544.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-24
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-05-24
AI Technical Summary
Acrylic foam tape is prone to residual pressure-sensitive adhesive when peeled off, affecting the bonding strength of electronic products and causing the bonding performance of new parts to electronic products to deteriorate.
Using raw materials such as terpene resin, organic rigid particles PA6 and bacterial cellulose, polymerization is initiated through initiators, crosslinking agents and lauryl glucosides, improve the cohesive strength and connection strength of acrylic pressure-sensitive adhesives, and reduce peeling Remaining.
It significantly reduces the residual rate of pressure-sensitive adhesive on electronic products after the acrylic foam tape is peeled off, improves the bonding strength between new parts and electronic products, and ensures stable performance after replacement of parts.
Smart Images

Figure GDA0004912980410000071 
Figure GDA0004912980410000081 
Figure GDA0004912980410000091
Abstract
Description
Technical Field
[0001] The present application relates to the field of adhesive tape applications, and more specifically, to an acrylic foam adhesive tape and a preparation method thereof. Background Art
[0002] Acrylic foam tape is usually made of acrylic foam as the base material, with solvent-based or hot-melt acrylic pressure-sensitive adhesive coated on one or both sides of the base material, and then covered with a release film. Acrylic foam tape can be used in different mechanical parts, mobile phone accessories, and computer electronic products to ensure the stability of electronic products in the production process.
[0003] Although solvent-based acrylic pressure-sensitive adhesives have good bonding properties, they are expensive and have a significant impact on the human body and the environment, so they are likely to be eliminated. Therefore, hot-melt acrylic pressure-sensitive adhesives have attracted great attention. In the related art, when replacing parts in electronic products, it is necessary to peel off the acrylic foam tape from the electronic products.
[0004] With respect to the above-mentioned related technologies, the inventors believe that when the acrylic foam tape is peeled off from the electronic product, residual pressure-sensitive adhesive is easily generated, which makes it difficult to remove the acrylic foam tape cleanly. The residual pressure-sensitive adhesive adheres to the electronic product, which will affect the bonding strength between the newly replaced parts and the electronic product, thereby affecting the use of the electronic product. Summary of the invention
[0005] In order to reduce the residual pressure-sensitive adhesive on the electronic product after peeling off the acrylic foam tape, so that the bonding strength between the newly replaced parts and the electronic product is not easily affected, the present application provides an acrylic foam tape and a preparation method thereof.
[0006] In a first aspect, the present application provides an acrylic foam tape, which adopts the following technical solution:
[0007] An acrylic foam tape comprises an acrylic foam substrate and an acrylic pressure-sensitive adhesive coated on one or both sides of the acrylic foam substrate, wherein the outer side of the acrylic pressure-sensitive adhesive is also covered with a release film, and the acrylic pressure-sensitive adhesive comprises the following raw materials in parts by weight:
[0008] 50-85 parts of soft monomer;
[0009] 20-40 parts of hard monomer;
[0010] 5-20 parts of functional monomer;
[0011] 0.8-2 parts of cross-linking agent;
[0012] 0.35-0.55 parts of initiator;
[0013] 3 to 10 parts of terpene resin;
[0014] 2 to 8 parts of organic rigid particles PA6;
[0015] 1.5 to 3.5 parts of bacterial cellulose.
[0016] By adopting the above technical scheme, on the basis of the raw materials of soft monomer, hard monomer, functional monomer, crosslinking agent and initiator, terpene resin, organic rigid particle PA6 and bacterial cellulose are added, and the terpene resin, organic rigid particle PA6 and bacterial cellulose are mixed and stirred evenly with the raw materials, and then the polymerization is initiated by the initiator. After the polymerization is completed, the crosslinking agent is added and mixed and stirred evenly to obtain an acrylic pressure-sensitive adhesive. Bacterial cellulose itself has a porous network structure, which can improve the connection strength between the raw materials at different positions in the acrylic pressure-sensitive adhesive. The addition of terpene resin can improve the compatibility between bacterial cellulose and other raw materials. Organic rigid particle PA6 promotes the dispersibility of bacterial cellulose and terpene resin during the reaction process, and reduces the situation where terpene resin and bacterial cellulose gather in one place during the stirring process. Therefore, the synergistic effect of the three can improve the cohesive strength of the acrylic pressure-sensitive adhesive itself, thereby reducing the residual pressure-sensitive adhesive on the electronic product after the acrylic foam tape is peeled off, so that the bonding strength between the newly replaced parts and the electronic product is not easily affected.
[0017] Optionally, the acrylic pressure-sensitive adhesive comprises the following raw materials in parts by weight:
[0018] 65-70 parts of soft monomer;
[0019] 25-35 parts of hard monomer;
[0020] 10-15 parts of functional monomer;
[0021] 1.2 to 1.6 parts of a cross-linking agent;
[0022] 0.4-0.5 parts of initiator;
[0023] 6-8 parts of terpene resin;
[0024] 4 to 6 parts of organic rigid particles PA6;
[0025] 2.5 to 3 parts of bacterial cellulose.
[0026] By adopting the above technical solution, when the raw materials are in the above combination ratio, the prepared acrylic pressure-sensitive adhesive has excellent cohesive strength.
[0027] Optionally, the particle size of the organic rigid particles PA6 is 5 to 15 μm.
[0028] By adopting the above technical scheme, when the particle size of the organic rigid particle PA6 is 5 to 15 μm, the organic rigid particle PA6 has few surface defects and has an excellent dispersion effect, thereby reducing the self-agglomeration of the terpene resin and making the organic rigid particle PA6 carry the terpene resin and be evenly dispersed among the raw materials of the acrylic pressure-sensitive adhesive.
[0029] Optionally, the acrylic pressure-sensitive adhesive further comprises 3 to 5 parts by weight of lauryl glucoside.
[0030] By adopting the above technical scheme, lauryl glucoside and the cross-linking agent work synergistically to achieve a penetration effect between the raw materials of the acrylic pressure-sensitive adhesive and enhance the connection strength between the raw materials. At the same time, lauryl glucoside can adhere to the interface of the acrylic pressure-sensitive adhesive, improve the overall permeability of the acrylic pressure-sensitive adhesive, and enhance the connection strength between the acrylic pressure-sensitive adhesive and the acrylic foam.
[0031] Optionally, the method for preparing the acrylic pressure-sensitive adhesive comprises the following steps:
[0032] A1. Mix soft monomer, hard monomer, functional monomer, terpene resin, organic rigid particle PA6 and bacterial cellulose in a certain ratio to obtain a mixture;
[0033] A2, using a portion of the total amount of the mixture obtained in A1 as a base material, adding an initiator, heating to a reaction temperature of 74°C to 84°C to initiate polymerization, and then adding the remaining mixture to carry out a polymerization reaction;
[0034] A3, after the polymerization reaction of A2 is completed, add the crosslinking agent, mix well and then discharge the material to obtain the acrylic pressure-sensitive adhesive.
[0035] By adopting the above technical scheme, the soft monomer, hard monomer, functional monomer, terpene resin, organic rigid particle PA6 and bacterial cellulose are first mixed evenly, so that the organic rigid particle PA6 can disperse the terpene resin and the cell cellulose well among the raw materials, and then a part of the mixture is added and heated, and a polymerization reaction is initiated under the initiation of benzoyl peroxide, and a cross-linking agent is added to improve the polymerization stability, so that an acrylic pressure-sensitive adhesive with excellent cohesive strength can be obtained.
[0036] Optionally, the method for preparing the acrylic pressure-sensitive adhesive comprises the following steps:
[0037] B1. Mix soft monomer, hard monomer, functional monomer, terpene resin, organic rigid particle PA6 and bacterial cellulose in a certain ratio to obtain a mixture;
[0038] B2, using a portion of the total amount of the mixture obtained in B1 as a base material, adding an initiator, heating to a reaction temperature of 74°C to 84°C to initiate polymerization, and then adding the remaining mixture to carry out a polymerization reaction;
[0039] B3. After the polymerization reaction of B2 is completed, add the crosslinking agent and lauryl glucoside, mix them evenly and then discharge the material to obtain the acrylic pressure-sensitive adhesive.
[0040] By adopting the above technical scheme, after the polymerization reaction of soft monomer, hard monomer, functional monomer, terpene resin, organic rigid particle PA6 and bacterial cellulose, a cross-linking agent and lauryl glucoside are added. Lauryl glucoside and the cross-linking agent act synergistically to promote the penetration of the cross-linking agent between the raw materials, so that the adhesion and curing of the acrylic pressure-sensitive adhesive are uniform, and the connection strength between the acrylic pressure-sensitive adhesive and the acrylic foam substrate is improved.
[0041] Optionally, the acrylic foam substrate comprises the following raw materials in parts by weight:
[0042] 100 parts of isooctyl acrylate;
[0043] 20-30 parts of acrylic acid;
[0044] 3-5 parts of photoinitiator;
[0045] 3-5 parts of polymerization regulator;
[0046] 2 to 5 parts of curing agent;
[0047] 10-15 parts of mica powder;
[0048] 0.3-0.7 parts of polyester fiber;
[0049] By adopting the above technical scheme, mica powder and polyester fiber are added on the basis of raw materials of isooctyl acrylate, acrylic acid, photoinitiator, polymerization regulator and curing agent. The mica powder can adhere to the surface of the polyester fiber, increase the surface roughness of the polyester fiber, and improve the connection strength between the polyester fiber and other raw materials in the acrylic foam substrate. At the same time, the mica powder adheres to the polyester fiber to better improve the tensile strength of the polyester fiber itself. The mica powder can also be used as a filler to fill the acrylic foam substrate, so that the acrylic foam substrate is more stable after curing, thereby improving the tensile strength of the acrylic foam substrate.
[0050] Optionally, the method for preparing the acrylic foam substrate comprises the following steps:
[0051] S1, taking isooctyl acrylate, acrylic acid, mica powder and polyester fiber according to the ratio and mixing them evenly to obtain a mixture, and adding a photoinitiator and a polymerization regulator to cause a polymerization reaction;
[0052] S2. After the polymerization reaction of S1 is completed, a curing agent is added to carry out a curing reaction. After the reaction is completed, an acrylic foam substrate is obtained.
[0053] By adopting the above technical scheme, isooctyl acrylate, acrylic acid, mica powder and polyester fiber are evenly mixed, and a polymerization reaction occurs under the action of a photoinitiator and a polymerization regulator. The mica powder adheres to the surface of the polyester fiber, which can better play the role of the polyester fiber in connecting the structures of various raw materials. The curing is completed under the action of a curing agent, so that the structure of the cured acrylic foam substrate is more stable, thereby improving the strength of the acrylic foam substrate.
[0054] In a second aspect, the present application provides a method for preparing an acrylic foam tape, using the following technical solution:
[0055] A method for preparing an acrylic foam tape comprises the following steps:
[0056] The acrylic pressure-sensitive adhesive is coated on one or both sides of an acrylic foam substrate, a release film is covered on the side of the acrylic pressure-sensitive adhesive away from the acrylic foam substrate, and the acrylic foam tape is prepared by heating in an oven at 80 to 110° C. for 4 to 6 hours.
[0057] By adopting the above technical solution, the acrylic pressure-sensitive adhesive is coated on one side or both sides of the acrylic foam substrate, and then the release film is covered on the acrylic pressure-sensitive adhesive, and the finished acrylic foam tape is obtained after heating in an oven.
[0058] In summary, this application has the following beneficial effects:
[0059] 1. Since the present application adopts terpene resin, organic rigid particles PA6 and bacterial cellulose, and since bacterial cellulose itself has a porous network structure, the connection strength between raw materials at different positions in the acrylic pressure-sensitive adhesive can be improved. The addition of terpene resin can improve the compatibility between bacterial cellulose and other raw materials. During the reaction, the organic rigid particles PA6 promote the dispersibility of bacterial cellulose and terpene resin, and reduce the situation where terpene resin and bacterial cellulose gather in one place during the stirring process. The three act synergistically to improve the cohesive strength of the acrylic pressure-sensitive adhesive itself, thereby reducing the residual pressure-sensitive adhesive on the electronic product after peeling off the acrylic foam tape, so that the bonding strength between the newly replaced parts and the electronic product is not easily affected; 2. Lauryl glucoside is preferably used in the present application. Due to the synergistic effect of lauryl glucoside and the cross-linking agent, it can play a penetration effect between the raw materials of the acrylic pressure-sensitive adhesive and enhance the connection strength between the raw materials. At the same time, lauryl glucoside can adhere to the interface of the acrylic pressure-sensitive adhesive, improve the overall permeability of the acrylic pressure-sensitive adhesive, and improve the connection strength between the acrylic pressure-sensitive adhesive and the acrylic foam;
[0060] 3. The method of the present application increases the surface roughness of the polyester fiber by first attaching mica powder to the surface of the polyester fiber, thereby improving the connection strength between the polyester fiber and other raw materials in the acrylic foam substrate. At the same time, the mica powder is attached to the polyester fiber to better improve the tensile strength of the polyester fiber itself. The mica powder can also be used as a filler to fill the acrylic foam substrate, making the acrylic foam substrate more stable after curing, thereby improving the strength of the acrylic foam substrate.
[0061] 4. Since bacterial cellulose and organic rigid particles PA6 are added in the present application, both bacterial cellulose and PA6 have certain water absorption, which can reduce the effect of humidity on the adhesion of acrylic pressure-sensitive adhesive. DETAILED DESCRIPTION
[0062] The present application is further described in detail with reference to the following examples. It is specially noted that if no specific conditions are specified in the following examples, the conventional conditions or the conditions recommended by the manufacturer are followed, and the raw materials used in the following examples can be obtained from common commercial sources unless otherwise specified.
[0063] Preparation Example
[0064] In this experiment, butyl acrylate was selected as the soft monomer, vinyl acetate as the hard monomer, acrylic acid as the functional monomer, toluene diisocyanate as the crosslinker, benzoyl peroxide as the initiator, and the width of the bacterial cellulose was 0.05 μm in the acrylic pressure-sensitive adhesive; 1-hydroxycyclohexyl phenyl ketone was selected as the photoinitiator, dodecanethiol as the polymerization regulator, and curing agent XR-500 as the curing agent for the acrylic foam substrate. The particle size of the mica powder was 8 μm, and the length of the polyester fiber was 6 mm and the diameter was 20 μm.
[0065] Preparation Example 1
[0066] A method for preparing an acrylic pressure-sensitive adhesive comprises the following steps:
[0067] A1, take 50g of butyl acrylate, 40g of vinyl acetate, 5g of acrylic acid, 3g of terpene resin, 2g of organic rigid particles PA6 with a particle size of 5μm, and 1.5g of bacterial cellulose, mix them evenly to obtain a mixture;
[0068] A2, using a portion of the total amount of the mixture obtained in A1 as a base material, adding 0.8 g of toluene diisocyanate, heating to a reaction temperature of 74°C to initiate polymerization, and then adding the remaining mixture to carry out a polymerization reaction;
[0069] A3, after the polymerization reaction of A2 is completed, add 0.35g of benzoyl peroxide, mix well and then discharge to obtain the acrylic pressure-sensitive adhesive.
[0070] Preparation Example 2
[0071] The difference between this preparation example and preparation example 1 is that the reaction temperature in step A2 is 84° C. and the weights of the raw materials are different, see Table 1 for details.
[0072] Preparation Example 3
[0073] The difference between this preparation example and preparation example 1 is that the reaction temperature in step A2 is 79° C., and the weight and particle size of each raw material are different, see Table 1 for details.
[0074] Preparation Example 4
[0075] The difference between this preparation example and preparation example 1 is that the reaction temperature in step A2 is 76° C., and the weight and particle size of each raw material are different, see Table 1 for details.
[0076] Preparation Example 5
[0077] The difference between this preparation example and preparation example 1 is that the reaction temperature in step A2 is 81° C., and the weight and particle size of each raw material are different, see Table 1 for details.
[0078] Preparation Example 6
[0079] The difference between this preparation example and preparation example 3 is that the particle size of the organic rigid particles PA6 is 3 μm.
[0080] Preparation Example 7
[0081] The difference between this preparation example and preparation example 3 is that the particle size of the organic rigid particles PA6 is 20 μm.
[0082] Preparation Example 8
[0083] The difference between this preparation example and preparation example 1 is that the particle size of the organic rigid particles PA6 is 3 μm.
[0084] Preparation Example 9
[0085] The difference between this preparation example and preparation example 5 is that the particle size of the organic rigid particles PA6 is 20 μm.
[0086] Preparation Example 10
[0087] The difference between this preparation example and preparation example 3 is that 3 g of lauryl glucoside is added in this preparation example.
[0088] Preparation Example 11
[0089] The difference between this preparation example and preparation example 3 is that 4.2 g of lauryl glucoside is added in this preparation example.
[0090] Preparation Example 12
[0091] The difference between this preparation example and preparation example 3 is that 5 g of lauryl glucoside is added in this preparation example.
[0092] Preparation Example 13
[0093] The difference between this preparation example and preparation example 3 is that this preparation example does not contain terpene resin, organic rigid particles PA6 and bacterial cellulose.
[0094] Preparation Example 14
[0095] The difference between this preparation example and preparation example 3 is that there is no terpene resin in this preparation example.
[0096] Preparation Example 15
[0097] The difference between this preparation example and preparation example 3 is that there is no organic rigid particle PA6 in this preparation example.
[0098] Preparation Example 16
[0099] The difference between this preparation example and preparation example 3 is that there is no bacterial cellulose in this preparation example.
[0100] Preparation Example 17
[0101] The difference between this preparation example and preparation example 3 is that there is no terpene resin and organic rigid particles PA6 in this preparation example.
[0102] Preparation Example 18
[0103] The difference between this preparation example and preparation example 3 is that there is no terpene resin and bacterial cellulose in this preparation example.
[0104] Preparation Example 19
[0105] The difference between this preparation example and preparation example 3 is that there is no terpene resin and bacterial cellulose in this preparation example.
[0106] Table 1
[0107]
[0108] Preparation Example 20
[0109] A method for preparing an acrylic foam substrate comprises the following steps:
[0110] B1, 100g of isooctyl acrylate, 20g of acrylic acid, 10g of mica powder and 0.3g of polyester fiber were mixed evenly to obtain a mixture, and 3g of 1-hydroxycyclohexyl phenyl ketone and 3g of dodecanethiol were added to cause polymerization reaction;
[0111] B2. After the polymerization reaction of B1 is completed, add 2g of curing agent XR-500 and perform UV lamp irradiation reaction under nitrogen conditions. The nitrogen pressure is 3 kg and the reaction speed is 100 rpm. After the reaction is completed, the acrylic foam substrate is obtained.
[0112] Preparation Example 21
[0113] The difference between this preparation example and preparation example 20 is that the weight of each raw material is different. The weight of each raw material is shown in Table 2.
[0114] Preparation Example 22
[0115] The difference between this preparation example and preparation example 20 is that the weight of each raw material is different. The weight of each raw material is shown in Table 2.
[0116] Preparation Example 23
[0117] The difference between this preparation example and preparation example 21 is that there is no mica powder and polyester fiber in this preparation example.
[0118] Preparation Example 24
[0119] The difference between this preparation example and preparation example 21 is that there is no mica powder in this preparation example.
[0120] Preparation Example 25
[0121] The difference between this preparation example and preparation example 21 is that there is no polyester fiber in this preparation example.
[0122] Table 2
[0123]
[0124] Example
[0125] Example 1
[0126] An acrylic foam tape comprises an acrylic foam substrate and an acrylic pressure-sensitive adhesive coated on one side or both sides of the acrylic foam substrate, wherein the outer side of the acrylic pressure-sensitive adhesive is also covered with a release film.
[0127] A method for preparing an acrylic foam tape comprises the following steps:
[0128] The acrylic pressure-sensitive adhesive prepared in Preparation Example 1 was coated on one or both sides of the acrylic foam substrate prepared in Preparation Example 23. In this embodiment, it was coated on both sides. A release film was covered on the side of the acrylic pressure-sensitive adhesive away from the acrylic foam substrate, and the acrylic foam tape was prepared by heating at 80° C. in an oven for 4 hours.
[0129] Embodiments 2 to 18
[0130] The difference between this embodiment and embodiment 1 is that the acrylic foam tape prepared by using acrylic pressure-sensitive adhesive and acrylic foam substrate of different preparation examples has different reaction temperature and treatment time, as shown in Table 3 for details.
[0131] Comparative Example
[0132] Comparative Examples 1 to 7
[0133] The difference between this comparative example and Example 1 is that the acrylic foam tape is prepared by using acrylic pressure-sensitive adhesives of different preparation examples, as shown in Table 3 for details.
[0134] Table 3
[0135]
[0136]
[0137] Performance testing
[0138] Test methods
[0139] 1. Using method 1 in the test method for peel strength of adhesive tape in GB / T 2792-2014, a peeling test was performed on the acrylic foam tapes prepared in each embodiment and comparative example, and the peeling speed was (300±10) mm / min.
[0140] 2. The acrylic foam tapes prepared in each embodiment and comparative example were prepared using Method 3 of GB / T 33332-2016 for dynamic shear strength of adhesive tapes. The preparation process is as follows:
[0141] Cut 5 adhesive tape samples and bond them to the test steel plate. The width and length of the adhesive tape samples are both 12±0.1mm. Use a roller to roll the bonding area of the sample back and forth along the length direction twice. The rolling speed is 10mm / s, and no additional pressure can be applied.
[0142] The shear strength of the test pieces prepared from the acrylic foam tapes prepared in each embodiment and comparative example was measured using a tensile testing machine according to Method 3 of Dynamic Shear Strength of Adhesive Tapes in GB / T 33332-2016, with a pulling rate of 5 mm / min until the test steel plate was completely separated.
[0143] The test results are shown in Table 4.
[0144] Table 4
[0145]
[0146]
[0147] Combining Example 3 and Comparative Example 1 and Table 4, it can be seen that the acrylic foam tape prepared in Example 3 is compared with the acrylic foam tape prepared in Comparative Example 1, and terpene resin, organic rigid particles PA6 and bacterial cellulose are added. According to the test results, the shear strength of the acrylic foam tape prepared in Comparative Example 3 is 1.36 times the shear strength of the acrylic foam tape prepared in Example 1, which shows that the acrylic foam tape prepared in Example 3 has high cohesive strength.
[0148] The peeling residual adhesive rate of the acrylic foam tape prepared in Comparative Example 1 is 11.27 times that of the acrylic foam tape prepared in Example 3, indicating that the acrylic foam tape prepared in Example 3 has a lower peeling residual adhesive rate.
[0149] The reasons are analyzed as follows: terpene resin, organic rigid particles PA6, bacterial cellulose and other raw materials are added and blended. The addition of terpene resin can improve the compatibility between bacterial cellulose and other raw materials. During the reaction, organic rigid particles PA6 promote the dispersion of bacterial cellulose and terpene resin among other raw materials and reduce the aggregation of terpene resin and bacterial cellulose in one place during stirring. Bacterial cellulose itself has a porous network structure, which can improve the connection strength between raw materials at different positions in the acrylic pressure-sensitive adhesive. The synergistic effect of the three improves the cohesive strength of the acrylic pressure-sensitive adhesive itself, thereby reducing the residual pressure-sensitive adhesive on the electronic product after peeling off the acrylic foam tape, making the bonding strength between the newly replaced parts and the electronic product less likely to be affected.
[0150] Combining Example 3, Comparative Examples 1 to 7 and Table 1 and Table 4, it can be seen that compared with the acrylic pressure-sensitive adhesive used in Comparative Example 1, the acrylic foam tape prepared in Example 3 adds terpene resin, organic rigid particles PA6 and bacterial cellulose, Comparative Example 2 only adds organic rigid particles PA6 and bacterial cellulose, Comparative Example 3 only adds terpene resin and bacterial cellulose, Comparative Example 4 only adds terpene resin and bacterial cellulose, Comparative Example 5 only adds bacterial cellulose, Comparative Example 6 only adds terpene resin, and Comparative Example 7 only adds bacterial cellulose.
[0151] According to the test results, the shear strength of the acrylic foam tape prepared in Example 3 is 1.13 to 1.36 times that of the acrylic foam tape prepared in Examples 1 to 7, the shear strength of the acrylic foam tape prepared in Example 3 is 1.24 to 1.32 times that of the acrylic foam tape prepared in Examples 5, 6, and 7, the peeling residual adhesive rate of the acrylic foam tape prepared in Examples 1 to 7 is 9 to 11.27 times that of the acrylic foam tape prepared in Example 3, and the peeling residual adhesive rate of the acrylic foam tape prepared in Examples 5, 6, and 7 is 10.46 to 10.81 times that of the acrylic foam tape prepared in Example 3, which reflects that when only one of terpene resin, organic rigid particles PA6 or bacterial cellulose is added, the peeling residual adhesive rate of the acrylic foam tape is not significantly reduced.
[0152] The shear strength of the acrylic foam tape prepared in Example 3 is 1.12 to 1.25 times that of the acrylic foam tape prepared in Examples 2, 3, and 4, and the peeling residual adhesive rate of the acrylic foam tape prepared in Examples 2, 3, and 4 is 9 to 10 times that of the acrylic foam tape prepared in Example 3, which shows that when only two of the three kinds of terpene resin, organic rigid particles PA6, and bacterial cellulose are added, the peeling residual adhesive rate of the acrylic foam tape is not significantly reduced. It shows that only when terpene resin, organic rigid particles PA6, and bacterial cellulose are added at the same time and act synergistically, can the peeling residual adhesive rate of the acrylic foam tape be significantly reduced, which can reduce the residual pressure-sensitive adhesive on the electronic product after peeling the acrylic foam tape, so that the bonding strength between the newly replaced parts and the electronic product is not easily affected.
[0153] It can be seen from Examples 1, 3, 5, 6, 7, 8, and 9 and Tables 1 and 4 that the particle size of the organic rigid particles PA6 in the acrylic foam tape prepared in Example 3 is 9 μm, the particle size of the organic rigid particles PA6 in the acrylic foam tape prepared in Example 1 is 5 μm, the particle size of the organic rigid particles PA6 in the acrylic foam tape prepared in Example 5 is 15 μm, the particle size of the organic rigid particles PA6 used in Examples 6 and 8 is 3 μm, and the particle size of the organic rigid particles PA6 used in Examples 7 and 9 is 20 μm. When the particle size of the organic rigid particles PA6 is too small, they are easy to agglomerate, resulting in excessive stress concentration in the acrylic foam tape; when the particle size of the organic rigid particles PA6 is too large, there are more surface defects and poor binding with terpene resin and bacterial cellulose, both of which are not conducive to reducing the peeling residue rate of the acrylic foam tape.
[0154] According to the test results, compared with the acrylic foam tape prepared in Example 3, the shear strength of the acrylic foam tape prepared in Example 6 was reduced by 4.6%, and the peeling residual rate was increased by 2.7%. The shear strength of the acrylic foam tape prepared in Example 7 was reduced by 9.2%, and the peeling residual rate was increased by 1.8%. Compared with the peeling residual rate of the acrylic foam tape prepared in Example 1, the shear strength of the acrylic foam tape prepared in Example 8 was reduced by 3.6%, and the peeling residual rate was increased by 2.1%. Compared with the peeling residual rate of the acrylic foam tape prepared in Example 5, the shear strength of the acrylic foam tape prepared in Example 9 was reduced by 5.0%, and the peeling residual rate was increased by 1.3%. It is reflected that the particle size restriction of the organic rigid particle PA6 can reduce the peeling residual rate of the acrylic foam tape.
[0155] It can be seen from Example 3, Examples 10 to 12 and Table 1 and Table 4 that, compared with Example 3, lauryl glucoside is added to the acrylic foam tapes prepared in Examples 10 to 12. From the test results, the shear strength of the acrylic foam tapes prepared in Examples 10 to 12 is increased by 1.31 to 1.44 times, and the peeling residual adhesive rate of the acrylic foam tapes prepared in Examples 10 to 12 is 0 to 0.2%, which is higher than the shear strength of the acrylic foam tape prepared in Example 3, and the peeling residual adhesive rate is significantly reduced, which reflects that the addition of lauryl glucoside can increase the connection strength between the acrylic pressure-sensitive adhesive and the acrylic foam substrate, thereby reducing the peeling residual adhesive rate of the acrylic foam tape.
[0156] The reason is that after the polymerization reaction, lauryl glucoside is added. Lauryl glucoside and the cross-linking agent work synergistically to promote the penetration of the cross-linking agent between the raw materials, so that the adhesion and curing of the acrylic pressure-sensitive adhesive are uniform, and the connection strength between the acrylic pressure-sensitive adhesive and the acrylic foam substrate is improved.
[0157] It can be seen from Example 11 and Example 14 and from Table 2 and Table 4 that the acrylic foam tape prepared in Example 14 has mica powder and polyester fiber added compared to the acrylic foam tape prepared in Example 11. From the test results, both show that there is no residual adhesive after peeling, and the acrylic foam substrate has no breakage. The shear strength of the acrylic foam tape prepared in Example 14 is 1.19 times that of the acrylic foam tape prepared in Example 11, which shows that the acrylic foam tape prepared in Example 3 has high strength.
[0158] Combining Examples 3, 11, 13, and 14 with Tables 2 and 4, it can be seen that Examples 3 and 11 use the acrylic foam substrate prepared in Preparation Example 23, while Examples 13 and 14 use the acrylic foam substrate prepared in Preparation Example 21. From the test results, compared with Example 3, Example 11 has a 2.6% reduction in the peeling residue rate of the acrylic foam tape, which is manifested as no residual glue after peeling and no damage to the acrylic foam substrate. Compared with Example 11, Example 14 has a 0% peeling residue rate of the acrylic foam tape, which is manifested as no residual glue after peeling and no damage to the acrylic foam substrate. This shows that the combination of mica powder and polyester fiber used in this application can improve the strength of the acrylic foam substrate.
[0159] The reason is analyzed as follows: mica powder adheres to the surface of polyester fiber, which increases the surface roughness of polyester fiber and improves the connection strength between polyester fiber and other raw materials in acrylic foam matrix. At the same time, mica powder adheres to polyester fiber, which better improves the tensile strength of polyester fiber itself. Mica powder can also be used as filler to fill acrylic foam matrix, making the acrylic foam matrix more stable after curing, thereby improving the strength of acrylic foam matrix.
[0160] It can be seen from Examples 11, 14 to 18 and Tables 2 and 4 that mica powder and polyester fiber are added to the acrylic foam tape prepared in Example 14, only polyester fiber is added to the acrylic foam tape prepared in Example 17, and only mica powder is added to Example 18. According to the test results, there is no residual glue after peeling, and the acrylic foam substrate is not damaged. The shear strength of the acrylic foam tape prepared in Example 17 is reduced by 12% compared with that prepared in Example 14, and the shear strength of the acrylic foam tape prepared in Example 18 is reduced by 13% compared with that prepared in Example 14, which is reflected in that only when mica powder and polyester fiber are added to the acrylic foam substrate at the same time and act synergistically, the strength of the acrylic foam substrate is more significantly improved.
[0161] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An acrylic foam tape, characterized in that: It includes an acrylic foam substrate and an acrylic pressure-sensitive adhesive coated on one side or both sides of the acrylic foam substrate, wherein the outer side of the acrylic pressure-sensitive adhesive is also covered with a release film, and the acrylic pressure-sensitive adhesive includes the following raw materials in parts by weight: 50-85 parts of soft monomer; 20-40 parts of hard monomer; 5-20 parts of functional monomer; 0.8-2 parts of cross-linking agent; 0.35-0.55 parts of initiator; 3 to 10 parts of terpene resin; 2 to 8 parts of organic rigid particles PA6; 1.5-3.5 parts of bacterial cellulose; The particle size of the organic rigid particles PA6 is 5 to 15 μm.
2. The acrylic foam tape according to claim 1, characterized in that: The acrylic pressure-sensitive adhesive comprises the following raw materials in parts by weight: 65-70 parts of soft monomer; 25-35 parts of hard monomer; 10-15 parts of functional monomer; 1.2 to 1.6 parts of a cross-linking agent; 0.4-0.5 parts of initiator; 6-8 parts of terpene resin; 4 to 6 parts of organic rigid particles PA6; 2.5-3 parts of bacterial cellulose; The particle size of the organic rigid particles PA6 is 5 to 15 μm.
3. An acrylic foam tape according to claim 2, characterized in that: The preparation method of the acrylic pressure-sensitive adhesive comprises the following steps: A1. Mix soft monomer, hard monomer, functional monomer, terpene resin, organic rigid particle PA6 and bacterial cellulose in a certain ratio to obtain a mixture; A2, using a portion of the total amount of the mixture obtained in A1 as a base material, adding an initiator, heating to a reaction temperature of 74°C to 84°C to initiate polymerization, and then adding the remaining mixture to carry out a polymerization reaction; A3, after the polymerization reaction of A2 is completed, add the crosslinking agent, mix well and then discharge the material to obtain the acrylic pressure-sensitive adhesive.
4. The acrylic foam tape according to claim 2, characterized in that: The acrylic pressure-sensitive adhesive further comprises 3 to 5 parts by weight of lauryl glucoside.
5. The acrylic foam tape according to claim 4, characterized in that: The preparation method of the acrylic pressure-sensitive adhesive comprises the following steps: B1. Mix soft monomer, hard monomer, functional monomer, terpene resin, organic rigid particle PA6 and bacterial cellulose in a certain ratio to obtain a mixture; B2, using a portion of the total amount of the mixture obtained in B1 as a base material, adding an initiator, heating to a reaction temperature of 74°C to 84°C to initiate polymerization, and then adding the remaining mixture to carry out a polymerization reaction; B3. After the polymerization reaction of B2 is completed, add the crosslinking agent and lauryl glucoside, mix them evenly and then discharge the material to obtain the acrylic pressure-sensitive adhesive.
6. The acrylic foam tape according to claim 3 or 5, characterized in that: The acrylic foam substrate comprises the following raw materials in parts by weight: 100 parts of isooctyl acrylate; 20-30 parts of acrylic acid; 3-5 parts of photoinitiator; 3-5 parts of polymerization regulator; 2 to 5 parts of curing agent; 10-15 parts of mica powder; 0.3-0.7 parts of polyester fiber.
7. The acrylic foam tape according to claim 6, characterized in that: The preparation method of the acrylic foam substrate comprises the following steps: S1, taking isooctyl acrylate, acrylic acid, mica powder and polyester fiber according to the ratio and mixing them evenly to obtain a mixture, and adding a photoinitiator and a polymerization regulator to cause a polymerization reaction; S2. After the polymerization reaction of S1 is completed, a curing agent is added to carry out a curing reaction. After the reaction is completed, an acrylic foam substrate is obtained.
8. The method for preparing an acrylic foam tape according to any one of claims 1 to 7, characterized in that: The acrylic pressure-sensitive adhesive is coated on one or both sides of an acrylic foam substrate, a release film is covered on the side of the acrylic pressure-sensitive adhesive away from the acrylic foam substrate, and the acrylic foam tape is prepared by heating in an oven at 80 to 110° C. for 4 to 6 hours.
Citation Information
Patent Citations
Foam adhesive tape and preparation method thereof
CN103254823A
Medical acrylate pressure-sensitive adhesive and preparation method thereof
CN104449414A